Production of free range chickens in the Spanish South-west - Duran, A. M.; Pascual, M. R. P. (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The object of this study is to elaborate a description of the products obtained from the breeding of free range chickens in the Spanish South-west, considering the possible sex influence. 24 Redstar Shaver chickens were used, 12 males and 12 females chickens. The animals were controlled weekly to determine productive yields when alive. After their slaughter, notes on carcasses and meats were taken. The males weighted more at the slaughter time and presented a better yield of the eviscerated carcass. The females showed a greater abdominal fat content and the regional composition was virtually the same in both sexes, however a greater percentage of legs was found in the males. The dissection of the inferior extremities showed a greater edible meat content in the females chickens. The organoLeptic tests (pH and water holding capacity CRA) presented relevant differences between sexes (greater pH and CRA. in the males). The comparison of the meat nutritive Value (protein and ashes) did not show relevant differences between males and females. This study shows that male and female chickens are products with similar nutritive value but distinguishable by other parameters.
The following values have no corresponding Zotero field: periodical: BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS issue: 90 pub-location: POSTBUS 220, 6700 AE WAGENINGEN, NETHERLANDS
Keywords: Dehesa; extensive chickens; production; Quality meat; sex poultry carcass

Production of free range chickens in the Spanish South-west - Duran, A M; Pascual, M R P (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The object of this study is to elaborate a description of the products obtained from the breeding of free range chickens in the Spanish South-west, considering the possible sex influence. 24 Redstar Shaver chickens were used, 12 males and 12 females chickens. The animals were controlled weekly to determine productive yields when alive. After their slaughter, notes on carcasses and meats were taken. The males weighted more at the slaughter time and presented a better yield of the eviscerated carcass. The females showed a greater abdominal fat content and the regional composition was virtually the same in both sexes, however a greater percentage of legs was found in the males. The dissection of the inferior extremities showed a greater edible meat content in the females chickens. The organoLeptic tests (pH and water holding capacity CRA) presented relevant differences between sexes (greater pH and CRA. in the males). The comparison of the meat nutritive Value (protein and ashes) did not show relevant differences between males and females. This study shows that male and female chickens are products with similar nutritive value but distinguishable by other parameters.
Keywords: Dehesa; extensive chickens; production; Quality meat; sex poultry carcass